The effect of π-Conjugation on the self-assembly of micelles and controlled cargo release - Yan Liang; Yalin Sun; Xiaoheng Fu; Yang Lin; Zhu Meng; Yanan Meng; Jiping Niu; Yusi Lai; Yong Sun (Artificial Cells, Nanomedicine, and Biotechnology)
Here we presented a novel micelle self-assembled from amphiphiles with π-conjugated moieties (OEG-DPH). The π-conjugated structural integrity of the micelles enabled stable encapsulation of Nile Red (NR, model drug). The self-assembly behaviour of the amphiphiles and the release profile of NR loaded micelles were investigated. Spherical core-shell structured NR loaded micelles with low CMC of 57 μg/mL and the efficient intracellular delivery process was monitored. This research provided a way to fabricate stable polymeric micelles and develop a practical nanocarrier for therapeutics delivery.